Ruthenium-based catalyst with high thermal stability, preparation method and application thereof

By combining polyol reduction method and rare earth oxide support, a high-thermal stability ruthenium-based catalyst was prepared, which solved the stability problem of Ru-based catalyst at high temperatures and achieved the effect of long-term and efficient catalytic ammonia decomposition reaction.

CN119771402APending Publication Date: 2025-04-08HANGZHOU TANFU NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510085416.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Ru-based catalysts have stability problems at high temperatures, resulting in a decrease in catalyst activity and irreversible inactivation, limiting their wide application in ammonia decomposition and hydrogen production reaction.

Method used

Ruthenium nanoparticles were prepared by polyol reduction method and loaded onto rare earth oxides. The silica limit domain was formed by high-temperature calcination treatment, thereby improving the thermal stability of the ruthenium-based catalyst.

Benefits of technology

The prepared high-thermally stable ruthenium-based catalyst maintained the reaction activity of 20,000 hours at 500°C, with a conversion rate of 99.5%, significantly extending the life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771402A_ABST
    Figure CN119771402A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalyst technology, and specifically to a ruthenium-based catalyst with high thermal stability, a preparation method and application thereof. (1) A ruthenium salt, a polyol and a surface protective agent are mixed and reacted to obtain a ruthenium nanoparticle colloid, wherein the polyol includes one of ethylene glycol, propylene glycol and isopropanol, and the surface protective agent includes one of trimethylsiloxane, aminosilane and dimethylpolysiloxane; (2) The ruthenium nanoparticle colloid described in step (1) is mixed with a rare earth oxide, and the ruthenium nanoparticles are loaded onto the rare earth oxide by a colloidal precipitation method to obtain a catalyst precursor; (3) The catalyst precursor is calcined to obtain the ruthenium-based catalyst. The ruthenium-based catalyst prepared by the present invention is applied to an ammonia decomposition reaction, and the reaction temperature is 500°C and 20,000 h. ‑1 Under the space velocity conditions, the catalyst reaction conversion rate can reach 99.5%, and the catalyst reaction activity remains basically unchanged when maintained at 500°C for 20,000 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a ruthenium-based catalyst with high thermal stability, a preparation method thereof and application thereof. Background Art

[0002] Ammonia decomposition hydrogen production catalyst technology plays an important role in the hydrogen energy industry. This technology produces hydrogen by decomposing ammonia into hydrogen and nitrogen, and is one of the key technologies in the field of hydrogen energy storage. In the technology of ammonia decomposition hydrogen production, the research and application of catalysts are crucial. At present, the main types of catalysts include Ru-based (ruthenium-based), Ni-based (nickel-based) and Fe-based (iron-based) catalysts. Among them, although Ni-based and Fe-based catalysts have lower costs, they generally have problems of high reaction temperature and high energy consumption, which limits their widespread application.

[0003] Among them, Ru-based catalysts have attracted much attention in the field of ammonia decomposition and hydrogen production due to their excellent catalytic activity. Ru-based catalysts can significantly reduce the activation energy of the ammonia decomposition and hydrogen production reaction, so that the ammonia decomposition reaction can be carried out efficiently at a relatively low temperature, about 500°C, which is significantly lower than the reaction temperature required by other catalysts. This high-efficiency catalytic performance at low temperatures brings many advantages. First, lowering the reaction temperature means an increase in energy conversion efficiency, because not too much energy is required to heat the reactants, thereby reducing overall energy consumption. Secondly, lower reaction temperatures can also reduce high temperature corrosion and wear on equipment, extending the service life of the equipment. In addition, low-temperature operation can also improve the purity of hydrogen, reduce the generation of by-products, and simplify the subsequent hydrogen purification process.

[0004] However, despite the outstanding performance of Ru-based catalysts in hydrogen production from ammonia decomposition, their application also faces some challenges. First, as a precious metal, ruthenium (Ru) has a relatively high market price, which directly leads to the high cost of Ru-based catalysts and limits their economic feasibility in large-scale industrial applications. Secondly, the stability of Ru-based catalysts at high temperatures is a key technical bottleneck. Under high-temperature reaction conditions, Ru catalyst particles are prone to sintering, that is, the catalyst particles aggregate and grow, resulting in a decrease in the catalyst surface area and the number of active sites, which leads to a significant decrease in catalyst activity. More seriously, the catalyst deactivation caused by this sintering is usually irreversible, which means that the catalyst cannot be restored to its original catalytic performance through a simple reactivation step. Therefore, in order to maintain the continuous progress of the reaction, the catalyst must be replaced regularly or the Ru precious metal in it must be recovered. The recovery process is not only complicated and costly, but may also involve the use of hazardous chemicals, causing potential environmental impacts. In addition, metal loss during the recovery process is also inevitable, further increasing the overall cost.

[0005] Therefore, although Ru-based catalysts have significant advantages in the hydrogen production reaction by ammonia decomposition, their high cost and stability issues at high temperatures remain the main obstacles restricting their widespread application. Summary of the invention

[0006] The present invention is made to solve the above-mentioned problems, and aims to provide a ruthenium-based catalyst with high thermal stability, a preparation method and application thereof.

[0007] The first aspect of the present invention provides a method for preparing a ruthenium-based catalyst with high thermal stability, characterized in that it comprises the following steps:

[0008] (1) mixing a ruthenium salt, a polyol and an organosilicon protective agent to react to obtain a ruthenium nanoparticle colloid, wherein the polyol comprises one of ethylene glycol, glycerol and isopropanol, and the organosilicon protective agent comprises one of trimethylsiloxane, aminosilane and dimethylpolysiloxane;

[0009] (2) mixing the ruthenium nanoparticle colloid described in step (1) with a rare earth oxide, and loading the ruthenium nanoparticles onto the rare earth oxide by a colloidal precipitation method to obtain a catalyst precursor;

[0010] (3) calcining the catalyst precursor to obtain the ruthenium-based catalyst.

[0011] The present invention adopts a polyol reduction method, and adopts a ruthenium salt as a ruthenium source mixed with a polyol. The ruthenium salt is reduced to metallic ruthenium in the polyol. The polyol acts as a reducing agent in this process to reduce ruthenium ions to metallic ruthenium. The polyol is oxidized in the reaction to generate aldehydes and / or acids, and releases electrons at the same time, which are used to reduce ruthenium ions. During the reduction process, metallic ruthenium atoms begin to gather to form nuclei, and then these nuclei gradually grow into ruthenium nanoparticles. At the same time, in this reaction, the polyol is not only a reducing agent, but also a solvent. The polyol can dissolve the ruthenium salt well, provide a uniform reaction medium, and help to form uniform ruthenium nanoparticles.

[0012] Furthermore, the addition of an organosilicon protective agent during the reaction can adsorb on the surface of the newly generated ruthenium nanoparticles to form a protective layer to prevent agglomeration between the particles, and stabilize the ruthenium nanoparticles through steric hindrance effect or charge repulsion effect, so that they remain dispersed in the solution.

[0013] Furthermore, the ruthenium nanoparticle colloid is mixed with a rare earth oxide, and the ruthenium nanoparticles are loaded onto a rare earth oxide carrier by a colloidal precipitation method, and subjected to a high-temperature calcination treatment to decompose the organosilicon protective agent in situ, so that the generated silica confines the ruthenium nanoparticles, and then the catalyst is reduced to obtain a ruthenium-based catalyst with high thermal stability confined by silica.

[0014] The present invention adjusts the particle size of the prepared ruthenium nanoparticles by adjusting the reaction conditions during the polyol reduction method, and adjusts the interaction between ruthenium and the carrier and the encapsulation of ruthenium by silicon dioxide by adjusting the roasting treatment conditions and the amount of organic silicon protection, thereby adjusting the microstructure and microenvironment of the active center ruthenium.

[0015] The ruthenium-based catalyst prepared by the present invention is applied to the ammonia decomposition reaction at 500°C and 20000h. -1 Under the space velocity condition, the catalyst reaction conversion rate can reach 99.5%, which is close to the reaction equilibrium conversion rate. And because the confinement of silica forms a confined coating locally on the ruthenium nanoparticles, the thermal stability of the catalyst can be greatly improved, and the catalyst life is increased. When kept at 500°C for 20,000 hours, the catalyst reaction activity remains basically unchanged.

[0016] In some embodiments, step (1) specifically includes: mixing a ruthenium salt, a polyol, an organosilicon protective agent and an alkaline reagent, and stirring the mixture at 160° C. to 200° C. for 2 to 4 hours under the protection of an inert gas to obtain the ruthenium nanoparticle colloid.

[0017] In the embodiment, the reaction is carried out under the protection of an inert gas (such as nitrogen or argon) to prevent the metal ruthenium from being oxidized at high temperature and to maintain its reduced state. At the same time, an alkaline reagent is used to neutralize the acidic substances in the reaction system to promote the reduction reaction.

[0018] In some embodiments, in step (1), the molar ratio of ruthenium element in the ruthenium salt to the organosilicon protective agent is 1:(5-15).

[0019] In the embodiment, by controlling the amount of the added organosilicon protective agent, silicon dioxide confinement can be formed on the surface of the ruthenium nanoparticles during the reaction, so that the catalyst has good thermal stability. If the organosilicon protective agent is excessive, excessive silicon dioxide may be generated, which will affect the interaction between Ru and rare earth oxides, affect electron transfer, and reduce activity. If the organosilicon protective agent is too little, insufficient silicon dioxide may be generated, and Ru cannot be fixed, and the purpose of confinement cannot be achieved.

[0020] In some embodiments, in step (1), the alkaline reagent is sodium hydroxide or sodium bicarbonate.

[0021] In some embodiments, the step (2) specifically includes: dispersing rare earth oxide in water, adding the ruthenium nanoparticle colloid, stirring for 24 to 32 hours, centrifugation washing, and drying at 60 to 120° C. for 8 to 24 hours to obtain the catalyst precursor.

[0022] In some embodiments, the rare earth oxide includes one of lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, lanthanum cerium oxide, and samarium cerium oxide.

[0023] In the embodiment, rare earth oxides are used as carriers. Since they have a large specific surface area, they can not only provide more active sites for the catalytic reaction, provide electrons to Ru, increase the rate of nitrogen desorption in ammonia decomposition, and improve the reaction activity, but also can well disperse the metal catalyst particles to prevent their sintering, maintain the activity and stability of the catalyst, and rare earth oxides have good thermal stability at high temperatures and are suitable for high-temperature catalytic processes.

[0024] In some embodiments, the step (3) specifically includes: placing the catalyst precursor in a muffle furnace, heating the temperature to 400-600°C at a heating rate of 2°C / min-10°C / min, maintaining the temperature for 2-4 hours, and obtaining the ruthenium-based catalyst after cooling.

[0025] In some embodiments, the mass fraction of the ruthenium active component in the ruthenium-based catalyst is 0.5% to 5%.

[0026] A second aspect of the present invention provides a ruthenium-based catalyst with high thermal stability, wherein the ruthenium-based catalyst with high thermal stability is prepared by the preparation method described in any one of the first aspects.

[0027] The third aspect of the present invention provides an application of a ruthenium-based catalyst with high thermal stability, characterized in that the ruthenium-based catalyst with high thermal stability prepared by any preparation method described in the first aspect or the ruthenium-based catalyst with high thermal stability described in the second aspect is subjected to a reaction at a reaction temperature of 400 to 600° C., a reaction pressure of 0 to 1 MPa, and a space velocity of 1000 to 50000 h -1 It is used to catalyze the decomposition of ammonia to produce nitrogen and hydrogen under conditions of .

[0028] By implementing the above technical solution, the present invention has the following beneficial effects:

[0029] The present invention adjusts the particle size of the prepared ruthenium nanoparticles by adjusting the reaction conditions during the polyol reduction method, and adjusts the interaction between ruthenium and the carrier and the encapsulation of ruthenium by silicon dioxide by adjusting the roasting treatment conditions and the amount of organic silicon protection, thereby adjusting the microstructure and microenvironment of the active center ruthenium.

[0030] The ruthenium-based catalyst prepared by the present invention is applied to the ammonia decomposition reaction at 500°C and 20000h. -1 Under the space velocity condition, the catalyst reaction conversion rate can reach 99.5%, which is close to the reaction equilibrium conversion rate. And because the confinement of silica forms a confined coating locally on the ruthenium nanoparticles, the thermal stability of the catalyst can be greatly improved, and the catalyst life is increased. When kept at 500°C for 20,000 hours, the catalyst reaction activity remains basically unchanged. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Transmission electron microscope image of the catalyst sample obtained in Example 1 of the present invention;

[0032] Figure 2 Particle size distribution diagram of ruthenium nanoparticles of the catalyst sample obtained in Example 1 of the present invention;

[0033] Figure 3 Transmission electron microscope image of the catalyst sample obtained in Example 2 of the present invention;

[0034] Figure 4 Particle size distribution diagram of ruthenium nanoparticles of the catalyst sample obtained in Example 2 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.

[0036] Example 1

[0037] (1) Preparation of Ruthenium Nanoparticle Colloid

[0038] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 6.45 g of trimethylsiloxane was dissolved therein to form a yellow transparent TMEOS-Ru 3+ -EG solution, the molar ratio of TMEOS monomer to Ru metal is 10:1 (i.e. TMEOS / Ru-10). 1 ml of 0.5 mol / L NaOH solution and 20 ml of Ru 3+ -TMEOS-EG solution, mixed evenly in a round-bottom flask, then stirred and refluxed at 160°C for 3 hours to fully react, i.e., 1.6nm Ru-TMEOS-EG solution. Its SEM electron microscope image is as follows Figure 1 As shown, the particle size of the ruthenium nanoparticles on the catalyst is about 1.6 nm.

[0039] (2) Catalyst 1.6nm RuCl 3 (TMEOS) / CeO 2 Preparation

[0040] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 1.6 nm Ru-TMEOS-EG solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 1.6 nm Ru(TMEOS) / CeO2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 1.6 nm Ru(TMEOS) / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.95wt%.

[0041] Example 2

[0042] (1) Preparation of Ruthenium Nanoparticle Colloid

[0043] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 6.45 g of trimethylsiloxane was dissolved therein to form a yellow transparent TMEOS-Ru 3+ -EG solution, the molar ratio of TMEOS monomer to Ru metal is 10:1 (i.e. TMEOS / Ru-10). 1 ml of 0.5 mol / L NaOH solution and 20 ml of Ru 3+ -TMEOS-EG solution, mixed evenly in a round-bottom flask, then stirred and refluxed at 198°C for 3 hours to fully react, i.e. 4.0nm Ru-TMEOS-EG solution. Its SEM electron microscope image is as follows Figure 3 As shown, the particle size of the ruthenium nanoparticles on the catalyst is about 4.0 nm.

[0044] (2) Catalyst 4.0nm RuCl 3 (TMEOS) / CeO 2 Preparation

[0045] Take 2g CeO 2 The carrier was dispersed in 50 ml of deionized water, and 5.58 ml of the 4.0 nm Ru-TMEOS-EG solution prepared above was added to the CeO2 aqueous solution. The mixture was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 ° C for 8 h to obtain a light gray powder, which was recorded as 4.0 nm Ru(TMEOS) / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 4.0 nm Ru(TMEOS) / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.93wt%.

[0046] Example 3

[0047] (1) Preparation of Ruthenium Nanoparticle Colloid

[0048] Weigh 1.3912g RuCl3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 6.45 g of aminosilane was dissolved therein to form a yellow transparent Aminosilane-Ru 3+ The molar ratio of Aminosilane monomer to Ru metal is 10:1 (i.e. Aminosilane / Ru-10). 1 ml of 0.5 mol / L NaOH solution is mixed with 20 ml of Ru 3+ -Aminosilane solution, mixed evenly in a round-bottom flask, and then stirred and refluxed at 160°C for 3 hours to fully react, i.e., 1.8 nm Ru-Aminosilane solution.

[0049] (2) Catalyst 1.8nm Ru-Aminosilane / CeO 2 Preparation

[0050] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 1.8 nm Ru-Aminosilane solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 ° C for 8 h to obtain a light gray powder, which was recorded as 1.8 nm Ru-Aminosilane / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 1.8 nm Ru-Aminosilane / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.95wt%.

[0051] Example 4

[0052] (1) Preparation of Ruthenium Nanoparticle Colloid

[0053] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 6.45 g of aminosilane was dissolved in 100 mL of ethylene glycol to form a yellow transparent Aminosilane-Ru 3+ The molar ratio of Aminosilane monomer to Ru metal is 10:1 (i.e. Aminosilane / Ru-10). 1 ml of 0.5 mol / L NaOH solution is mixed with 20 ml of Ru 3+-Aminosilane solution, mixed evenly in a round-bottom flask, and then stirred and refluxed at 198°C for 3 hours to obtain a 4.1 nm Ru-Aminosilane solution.

[0054] (2) Catalyst 4.1nm Ru-Aminosilane / CeO 2 Preparation

[0055] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 4.1 nm Ru-Aminosilane solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 ° C for 8 h to obtain a light gray powder, which was recorded as 4.1 nm Ru-Aminosilane / CeO 2 The precursor was placed in a muffle furnace and heated to 500 °C at a heating rate of 5 °C / min and maintained for 4 h to obtain 4.1 nm Ru-Aminosilane / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.94wt%.

[0056] Example 5

[0057] (1) Preparation of Ruthenium Nanoparticle Colloid

[0058] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 52.3 g of dimethyl polysiloxane was dissolved therein to form a yellow transparent PDMS-Ru 3+ -EG solution, the molar ratio of PDMS monomer to Ru metal is 10:1 (i.e. PDMS / Ru-10). 1 ml of 0.5 mol / L NaOH solution and 20 ml of Ru 3+ -PDMS-EG solution, mix well in a round-bottom flask, and then stir and reflux at 160 °C for 3 hours to fully react, i.e., 2.0 nm Ru-PDMS-EG solution.

[0059] (2) Catalyst 2.0nm Ru-PDMS-EG / CeO 2 Preparation

[0060] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 2.0 nm Ru-PDMS-EG solution prepared above was added to the CeO 2The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 2.0 nm Ru-PDMS / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 2.0 nm Ru-PDMS / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.96wt%.

[0061] Example 6

[0062] (1) Preparation of Ruthenium Nanoparticle Colloid

[0063] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 52.3 g of dimethyl polysiloxane was dissolved therein to form a yellow transparent PDMS-Ru 3+ -EG solution, the molar ratio of PDMS monomer to Ru metal is 10:1 (i.e. PDMS / Ru-10). 1 ml of 0.5 mol / L NaOH solution and 20 ml of Ru 3+ -PDMS-EG solution, mix well in a round-bottom flask, and then stir and reflux at 198 °C for 3 hours to fully react, i.e., 4.4 nm Ru-PDMS-EG solution.

[0064] (2) Catalyst 4.4nm Ru-PDMS-EG / CeO 2 Preparation

[0065] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 4.4 nm Ru-PDMS-EG solution prepared above was added to the CeO 2 The mixture was stirred at room temperature for 24 h, washed three times by centrifugation with deionized water and ethylene glycol alternately, and the resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 4.4 nm Ru-PDMS / CeO 2 The precursor was placed in a muffle furnace and heated to 500 °C at a heating rate of 5 °C / min and maintained for 4 h to obtain 4.4 nm Ru-PDMS / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.95wt%.

[0066] Example 7

[0067] (1) Preparation of Ruthenium Nanoparticle Colloid

[0068] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 5.15 g of trimethylsiloxane was dissolved therein to form a yellow transparent TMEOS-Ru 3+ -EG solution, the molar ratio of TMEOS monomer to Ru metal is 8:1 (i.e. TMEOS / Ru-10). 1 ml of 0.5 mol / L NaOH solution and 20 ml of Ru 3+ -TMEOS-EG solution, mixed evenly in a round-bottom flask, and then stirred and refluxed at 160°C for 3 hours to fully react, i.e., 1.7 nm Ru-TMEOS-EG solution.

[0069] (2) Catalyst 1.7nm RuCl 3 (TMEOS) / CeO 2 Preparation

[0070] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 1.7 nm Ru-TMEOS-EG solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 1.7 nm Ru(TMEOS) / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 1.7 nm Ru(TMEOS) / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.95wt%.

[0071] Comparative Example 1

[0072] (1) Preparation of Ruthenium Nanoparticle Colloid

[0073] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 1 ml of 0.5 mol / L NaOH solution was mixed with 20 ml of Ru 3+ The solution was mixed evenly in a round-bottom flask, and then stirred and refluxed at 160°C for 3 hours to obtain a 1.6 nm Ru solution.

[0074] (2) Catalyst 1.6nm RuCl 3 / CeO 2 Preparation

[0075] Take 2g CeO 2The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 1.6 nm Ru solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 1.6 nm Ru / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 1.6 nm Ru / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.93wt%.

[0076] Comparative Example 2

[0077] (1) Preparation of Ruthenium Nanoparticle Colloid

[0078] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 1 ml of 0.5 mol / L NaOH solution was mixed with 20 ml of Ru 3+ The solution was mixed evenly in a round-bottom flask, and then stirred and refluxed at 198°C for 3 hours to obtain a 4.0 nm Ru solution.

[0079] (2) Catalyst 4.0nm RuCl 3 / CeO 2 Preparation

[0080] Take 2g CeO 2 The carrier was dispersed in 50 ml of deionized water, and 5.58 ml of the 4.0 nm Ru solution prepared above was added to the CeO2 aqueous solution. The mixture was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 ° C for 8 h to obtain a light gray powder, which was recorded as 4.0 nm Ru / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 4.0 nm Ru / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.95wt%.

[0081] Comparative Example 3

[0082] (1) Preparation of Ruthenium Nanoparticle Colloid

[0083] Weigh 1.3912g RuCl 3 ·3H 2O was dispersed in 150 mL of ethylene glycol, and 1 ml of 0.5 mol / L NaOH solution was mixed with 20 ml of Ru 3+ The solution was mixed evenly in a round-bottom flask, and then stirred and refluxed at 160°C for 3 hours to obtain a 1.8 nm Ru solution.

[0084] (2) Catalyst 1.8nm Ru / CeO 2 Preparation

[0085] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 1.8 nm Ru solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 1.8 nm Ru / CeO 2 The mass content of Ru in the catalyst obtained by ICP elemental analysis was 0.94wt%.

[0086] Comparative Example 4

[0087] (1) Preparation of Ruthenium Nanoparticle Colloid

[0088] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 1 ml of 0.5 mol / L NaOH solution was mixed with 20 ml of Ru 3+ The solution was mixed evenly in a round-bottom flask, and then stirred and refluxed at 198°C for 3 hours to obtain a 4.1 nm Ru solution.

[0089] (2) Catalyst 4.1nm Ru / CeO 2 Preparation

[0090] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 4.1 nm Ru solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 4.1 nm Ru / CeO 2 The mass content of Ru in the catalyst obtained by ICP elemental analysis was 0.93wt%.

[0091] Comparative Example 5

[0092] (1) Preparation of Ruthenium Nanoparticle Colloid

[0093] Weigh 1.3912g RuCl3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 1 ml of 0.5 mol / L NaOH solution was mixed with 20 ml of Ru 3+ The solution was mixed evenly in a round-bottom flask, and then stirred and refluxed at 160°C for 3 hours to obtain a 2.0 nm Ru solution.

[0094] (2) Catalyst 2.0nm Ru / CeO 2 Preparation

[0095] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 2.0 nm Ru solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 2.0 nm Ru / CeO 2 The mass content of Ru in the catalyst obtained by ICP elemental analysis was 0.95wt%.

[0096] Comparative Example 6

[0097] (1) Preparation of Ruthenium Nanoparticle Colloid

[0098] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 1 ml of 0.5 mol / L NaOH solution was mixed with 20 ml of Ru 3+ The solution was mixed evenly in a round-bottom flask, and then stirred and refluxed at 198°C for 3 hours to obtain a 4.4 nm Ru solution.

[0099] (2) Catalyst 4.4nm Ru / CeO 2 Preparation

[0100] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 4.4 nm Ru solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 4.4 nm Ru / CeO 2 The mass content of Ru in the catalyst obtained by ICP elemental analysis was 0.94wt%.

[0101] Comparative Example 7

[0102] (1) Preparation of Ruthenium Nanoparticle Colloid

[0103] Weigh 1.3912g RuCl 3 ·3H 2 O was dispersed in 150 mL of ethylene glycol, and 12.89 g of trimethylsiloxane was dissolved therein to form a yellow transparent TMEOS-Ru 3+ -EG solution, the molar ratio of TMEOS monomer to Ru metal is 20:1 (i.e. TMEOS / Ru-10). 1 ml of 0.5 mol / L NaOH solution and 20 ml of Ru 3+ -TMEOS-EG solution, mixed evenly in a round-bottom flask, and then stirred and refluxed at 160°C for 3 hours to fully react, i.e., 1.5 nm Ru-TMEOS-EG solution.

[0104] (2) Catalyst 1.8nm RuCl 3 (TMEOS) / CeO 2 Preparation

[0105] Take 2g CeO 2 The support was dispersed in 50 ml of deionized water, and 5.58 mL of the 1.8 nm Ru-TMEOS-EG solution prepared above was added to the CeO 2 The solution was stirred at room temperature for 24 h, and washed three times by centrifugation with deionized water and ethylene glycol alternately. The resulting precipitate was vacuum dried at 60 °C for 8 h to obtain a light gray powder, which was recorded as 1.8 nm Ru(TMEOS) / CeO 2 The precursor was placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min and maintained for 4 h to obtain 1.5 nm Ru(TMEOS) / CeO 2 The mass content of Ru in the catalyst obtained by ICP element analysis is 0.95wt%.

[0106] Performance Testing

[0107] The highly thermally stable ruthenium-based catalysts prepared in Examples 1-7 and the catalysts prepared in Comparative Examples 1-7 were used to evaluate the ammonia decomposition hydrogen production reaction.

[0108] Test steps: The catalyst is loaded on a fixed bed reactor; ammonia is charged into the fixed bed reactor, and the ammonia space velocity is 1000-10000h -1 Under the conditions of , the reaction temperature is 500-600°C, the reaction pressure is 0-0.5MPa, and ammonia is decomposed into hydrogen and nitrogen.

[0109] Evaluation conditions: catalyst loading 5 ml, reaction ammonia space velocity 5000 h -1 , ammonia gas flow rate 416 ml / min, reaction temperature 500°C, reaction pressure 0.1 MPa.

[0110] Table 1 Test results

[0111]

[0112] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A method for preparing a ruthenium-based catalyst with high thermal stability, characterized in that: The following steps are involved: (1) mixing a ruthenium salt, a polyol and an organosilicon protective agent to react to obtain a ruthenium nanoparticle colloid, wherein the polyol comprises one of ethylene glycol, glycerol and isopropanol, and the organosilicon protective agent comprises one of trimethylsiloxane, aminosilane and dimethylpolysiloxane; (2) mixing the ruthenium nanoparticle colloid described in step (1) with a rare earth oxide, and loading the ruthenium nanoparticles onto the rare earth oxide by a colloidal precipitation method to obtain a catalyst precursor; (3) calcining the catalyst precursor to obtain the ruthenium-based catalyst.

2. The preparation method according to claim 1, characterized in that: Step (1) specifically comprises: mixing ruthenium salt, polyol, organosilicon protective agent and alkaline reagent, stirring and reacting at 160° C. to 200° C. for 2 to 4 hours under the protection of inert gas to obtain the ruthenium nanoparticle colloid.

3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of ruthenium element in the ruthenium salt to the organosilicon protective agent is 1:(5-15).

4. The preparation method according to claim 3, characterized in that: In step (1), the alkaline reagent is sodium hydroxide or sodium bicarbonate.

5. The preparation method according to claim 1, characterized in that: The step (2) specifically comprises: dispersing rare earth oxide in water, adding the ruthenium nanoparticle colloid, stirring for 24 to 32 hours, centrifugation washing, and drying at 60 to 120° C. for 8 to 24 hours to obtain the catalyst precursor.

6. The preparation method according to claim 5, characterized in that: The rare earth oxide includes one of lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, samarium oxide, lanthanum cerium oxide and samarium cerium oxide.

7. The preparation method according to claim 6, characterized in that: The step (3) specifically comprises: placing the catalyst precursor in a muffle furnace, heating the temperature to 400-600° C. at a heating rate of 2° C. / min-10° C. / min, maintaining the temperature for 2-4 hours, and obtaining the ruthenium-based catalyst after cooling.

8. The preparation method according to claim 7, characterized in that: The mass fraction of the ruthenium active component in the ruthenium-based catalyst is 0.5% to 5%.

9. A ruthenium-based catalyst with high thermal stability, characterized in that: The ruthenium-based catalyst with high thermal stability is prepared by the preparation method described in any one of claims 1 to 8.

10. Application of a ruthenium-based catalyst with high thermal stability, characterized in that: The ruthenium-based catalyst with high thermal stability prepared by the preparation method according to any one of claims 1 to 8 or the ruthenium-based catalyst with high thermal stability according to claim 9 is subjected to a reaction at a reaction temperature of 400 to 600° C., a reaction pressure of 0 to 1 MPa, and a space velocity of 1000 to 50000 h -1 It is used to catalyze the decomposition of ammonia to produce nitrogen and hydrogen under conditions of .

Citation Information

Cited By

  • High-stability catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of high-stability catalyst

    CN121402158A